Analisis Potensi Kandungan Tanaman Obat untuk Menunjang Kesehatan Santri - Jannah, Husnul; Masiah, Masiah (Bioscientist : Jurnal Ilmiah Biologi, 2020)
Research on the potential analysis of medicinal plant content has been carried out to support the health of students at the Nurul Islam Sekarbela Islamic Boarding School, Mataram City. Primary data collection is carried out by involving the community through interviews with local community groups and individual community members. The selection criteria were based on the informants' abilities and traditional medical practices. In data collection, the interview technique used was "open ended". This data collection technique is also used to explore knowledge systems regarding the diversity of types of traditional medicinal plants, management methods, their use, and community interest in medicinal plants using medicinal plants. Then it is enriched through secondary data in research, namely books / literature related to health, medicinal plants, journals, and other readings related to research. Based on the results of the interview, the names of medicinal plants commonly used in the community are obtained, including: Shallots (Allium cepa var. Aggregatum), Betel (Piper betle L.), Ginger (Zingiber officinale), Jatropha leaves (Jatropha curcas L. ), Guava (Psidium guajava linn), Turi leaves (Sesbania grandiflora), Lime (Citrus aurantifolia s), Katuk leaves (Sauropus androgynous), Banten (Lannea coromandelica), Kencur (Kaempferia galangal), Lengkuas (Alpinia galangal), Cat whiskers (Orthosiphon aristatus), horse whip (Stachytarpheta jamaicensis L.), Aloe vera (Aloe vera L), Yellow pumpkin (Cucurbita moschata), Papaya (Carica papaya L.), Wuluh starfruit (Averrhoa bilimbi), Cinnamon (Cinnamomum burmanii), Temulawak (Curcuma xanthorrhiza), Celery (Apium graveolens), soursop leaves (Annona muricata Linn), and lemongrass (Chymbopogon nardus L.). After analyzing the potential content of medicinal plants from journals, books, and other references related to medicinal plants, it was found that medicinal plants that can treat upper respiratory tract infections are turi leaves (Sesbania grandiflora) and shallots (Allium cepa var. Aggregatum). Medicinal plants that have the potential to treat skin diseases are lemongrass (Cymbopogon nardus L), Jatropha curcas L), Aloe vera (Aloe vera L.), and cinnamon (Cinnamomi burmannii Blume). Medicinal plants that have the potential to increase the body's immune system include: cat whiskers (Orthosiphon aristatus), Betel (Piper betle L.), lime (Citrus aurantifolia s), Temulawak (Curcuma xanthorrhiza), galangal (Alpinia galangal), and kencur (Kaempferia galangal). ). Medicinal plants that have the potential to treat digestive disorders are: Ginger (Zingiber officinale Rosc.) And soursop leaves (Annona muricata Linn). Meanwhile, medicinal plants that have the potential to treat oral diseases are: celery (Apium graveolens L.), papaya leaves (Carica papaya L.), and Betel (Piper betle L.).